MicroRNAs in Cerebral Ischemia - Yang Wang; Yongting Wang; Guo-Yuan Yang (Stroke Research and Treatment)
The risk of ischemic stroke increases substantially with age, making it the third leading cause of death and the leading cause of long-term disability in the world. Numerous studies demonstrated that genes, RNAs, and proteins are involved in the occurrence and development of stroke. Current studies found that microRNAs (miRNAs or miRs) are also closely related to the pathological process of stroke. miRNAs are a group of short, noncoding RNA molecules playing important role in posttranscriptional regulation of gene expression and they have emerged as regulators of ischemic preconditioning and ischemic postconditioning. Here we give an overview of the expression and function of miRNAs in the brain, miRNAs as biomarkers during cerebral ischemia, and clinical applications and limitations of miRNAs. Future prospects of miRNAs are also discussed.